2021
DOI: 10.1111/pedi.13149
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to oral glucose tolerance testing in children in stage 1 of type 1 diabetes: The TEDDY study

Abstract: Objective To examine adherence to the oral glucose tolerance test (OGTT) in multiple islet autoantibody children in stage 1 of developing type 1 diabetes (T1D). Methods Children are followed from birth in The Environmental Determinants of Diabetes in the Young (TEDDY) study. Completion of an OGTT is recommended every 6 months in children ≥3 years of age who are multiple islet autoantibody positive. Factors associated with adherence to the OGTT protocol were examined. Results The average subject level adherence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…As a consequence, intervention trials may identify different factors associated with parental study satisfaction. However, the association of parent study satisfaction to both study retention and compliance [ 14 , 15 , 19 , 20 ], suggests that the identification of factors associated with parent study satisfaction is important to the design of pediatric research studies. This study has numerous strengths in this regard, including a large sample size from four different countries, assessment of both mothers’ and fathers’ study satisfaction across long periods of time, use of a reliable measure of study satisfaction, and a comprehensive analysis of multiple factors for possible association with parental study satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, intervention trials may identify different factors associated with parental study satisfaction. However, the association of parent study satisfaction to both study retention and compliance [ 14 , 15 , 19 , 20 ], suggests that the identification of factors associated with parent study satisfaction is important to the design of pediatric research studies. This study has numerous strengths in this regard, including a large sample size from four different countries, assessment of both mothers’ and fathers’ study satisfaction across long periods of time, use of a reliable measure of study satisfaction, and a comprehensive analysis of multiple factors for possible association with parental study satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The Environmental Determinants of Diabetes in the Young (TEDDY) study was designed to identify environmental triggers of type 1 diabetes in genetically at-risk children from birth to 15 years of age. Using the DPT-1 methodology, TEDDY monitors parent study satisfaction on an ongoing basis and has found it to be associated with both study retention [ 14 ] and adherence with OGTT assessments [ 15 ], but not food record compliance [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, intervention trials may identify different factors associated with parent study satisfaction. However, the association of parent study satisfaction to both study retention and compliance (14,15,19,20), suggests that the identi cation of factors associated with parent study satisfaction is important to the design of pediatric research studies. This study has numerous strengths in this regard: a large sample size from four different countries; assessment of both mothers' and fathers' study satisfaction across long periods of time; use of a reliable measure of study satisfaction, and a comprehensive analysis of multiple factors for possible association with parent study satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Since study retention and compliance are associated with parents study satisfaction (14,15,19,20), identifying factors associated with parent study satisfaction is important to the design of pediatric research studies. Factors that are potentially modi able are particularly important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation